Self-assembly of a supramolecular square between [ni(dppe)(tof)2] and 4,4'-bipyridine (2013)
The main interest of this research is to contribute to the development and understanding of supramolecular chemistry and molecular architectures, which are constructed by the self-assembly of supramolecular entities. Therefore, the synthesis and characterization (IR, UV, 1H NMR, 31P, 19F, 1H-1H COSY) of a nickel (II) supramolecular square [7] was performed through the synthesis between nickel chloride [1] and diphenylphosphinoethane (dppe) [2] to form the precursor complex [Ni(dppe)Cl2] [3]. This was followed by the synthesis of the complex of interest, [Ni(dppe)(TOF)2] [5], using the precursor and silver trifluoromethanesulfonate (Ag-TOF). Finally, the self-assembly was performed between the complex [1,2-bis(diphenylphosphinoethane)bistriflatonickel(II)] [Ni(dppe)(OSO2CF3)2] [5] and the organic ligand 4,4'-bipyridine [6], which act as vertex and edge, respectively.According to various analyses, it was found that the self-assembly generated only one supramolecular species; a square is the most probable thermodynamic structure.